2020
DOI: 10.1101/2020.12.04.411702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADAR1 interaction with Z-RNA promotes editing of endogenous double-stranded RNA and prevents MDA5-dependent immune activation

Abstract: SummaryLoss-of-function of ADAR1 causes the severe autoinflammatory disease Aicardi-Goutières Syndrome (AGS). ADAR1 converts adenosines into inosines within double-stranded (ds) RNA. This process called A-to-I editing masks self-dsRNA from detection by the antiviral dsRNA sensor MDA5. ADAR1 binds to dsRNA in both the canonical A-form and in the poorly defined Z-conformation (Z-RNA). Mutations in the Z-RNA binding Zα-domain of ADAR1 are common in AGS patients. How loss of ADAR1/Z-RNA interaction contributes to … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Subsequent experiments demonstrated that the mouse equivalent to the P193A variant recapitulated the human Zα mendelian phenotype [36]. Three other recently generated mouse models using different loss of function Zα residues variants also were associated with a type I interferon signature [37][38][39]. Taken together, the data confirmed the biological relevance of the Z-conformation and provided evidence for its role in the regulation of type I interferon responses.…”
Section: Adar1 and Human Diseasementioning
confidence: 70%
See 2 more Smart Citations
“…Subsequent experiments demonstrated that the mouse equivalent to the P193A variant recapitulated the human Zα mendelian phenotype [36]. Three other recently generated mouse models using different loss of function Zα residues variants also were associated with a type I interferon signature [37][38][39]. Taken together, the data confirmed the biological relevance of the Z-conformation and provided evidence for its role in the regulation of type I interferon responses.…”
Section: Adar1 and Human Diseasementioning
confidence: 70%
“…Then p150 stays mostly cytoplasmic as nuclear uptake is inhibited by the free dsRNA that accumulates in the absence of p110. This explanation is supported by the finding that in the Zα loss of function mice, which have normal p110 levels, the nuclear and cytoplasmic levels of p150 are the same as wild type [37].…”
Section: The Importance Of Adar1 P150mentioning
confidence: 80%
See 1 more Smart Citation
“…RNA that adopts a non-canonical Z-conformation has increased immunostimulatory potential. The latter is reduced upon binding and editing by ADAR1 p150, which contains a Z-nucleic acid (Za) binding domain (de Reuver et al, 2021;Tang et al, 2021;Nakahama et al, 2021;Maurano et al, 2021;Zillinger & Bartok, 2021). In mice, various mutations in the Za domain of ADAR1 result in postnatal growth retardation and mortality as well as an increased type I IFN signature (de Reuver et al, 2021;Maurano et al, 2021;Nakahama et al, 2021;Tang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, when other cell death pathways are inactivated by mutation, necroptosis that is dependent on ZBP1 produces inflammation and disease due to necroptosis. Other labs (Jon Maelfait [ 21 ], Jan Rehwinkel [ 22 ] and Andrew Oberst (unpublished) presented studies from mouse models to examine the genetic interactions between ZBP1, MDA5 and ADAR1 and their outcomes, in particular on live births. Preliminary results were presented showing that in certain crosses, embryonic lethality was associated with high interferon responses in the mother but not dependent on the paternal genotype.…”
Section: Meeting Summarymentioning
confidence: 99%